'Rational use' in Antarctic waters. (January 2016) - Jacquet, Jennifer; Blood-Patterson, Eli; Brooks, Cassandra; Ainley, David
Abstract: The Convention for the Conservation of Antarctic Marine Living Resources (CAMLR Convention) is the legal doctrine presiding over the exploitation of marine life in the Southern Ocean. At recent Commission (CCAMLR) meetings, some member states have interpreted the term 'rational use' in the Convention text as 'the unrestricted right to fish' and, most recently, the term has been evoked in opposition to the establishment of marine protected areas. Tensions over interpretation of the term at CCAMLR are tracked and presented. The term's meaning and original intent are also explored in the publicly available record of treaty negotiations. According to negotiation documents as well as the CAMLR Convention, the term 'rational use' does not imply an unconditional right to exploit marine life in the Southern Ocean. Like 'scientific uncertainty, ' which has also been evoked in ways that reflect social values, 'rational use' should be seen as a value-laden term, rather than as an explicit mandate to fish. Highlights: Some members to CCAMLR have evoked the term 'rational use' used in the Convention text in opposition to the establishment of MPAs in Antarctica. Tensions over the interpretation of this are tracked and presented, as are the historical use and original intent of 'rational use'. There is no legal basis for the interpretation of 'rational use' as 'the unrestricted right to fish'.